Technological Gap Analysis of a Health Data Recording System for Older Adults and Enhancement Guidelines toward Digital Health Systems - สุวรรณหงษ์ สุภัทรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The transition toward an aging society has introduced significant challenges in health data management and the continuous monitoring of chronic diseases. This academic article aims to analyze a mobile-based health data recording system for older adults, developed on the Android platform, using a technological analysis framework. The analysis is conducted to compare the system’s characteristics with those of contemporary health applications and to identify technological gaps in terms of system architecture, data interoperability, data governance, and analytical capabilities. The system was originally developed following the System Development Life Cycle (SDLC) methodology. The study involved three experts and 399 users as participants. The evaluation results indicated a high level of user satisfaction (mean = 4.32, standard deviation = 0.61), reflecting the system’s appropriateness for use among older adults. However, within the context of contemporary digital health technologies, health applications have evolved toward integrated platform-based systems capable of connecting medical devices via internet networks, supporting cloud-based data processing, and utilizing artificial intelligence for advanced data analytics. The findings from this analysis reveal that, although the existing system demonstrates strengths in usability and effectively supports personal health data recording, it remains limited in terms of interoperability with international standards, multi-source data integration, and the application of advanced analytics technologies. Therefore, this article proposes strategic directions for transforming the system from a standalone application into an interoperable and scalable digital health platform. This study contributes academically by bridging applied system development with systematic technological analysis and contributes practically by providing a development roadmap for digital health systems tailored to older adults in alignment with global health technology trends.